Assessment of Social Responsibility (CSR) by the Spanish society: looking to the past to predict the future (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper examines the evolution of the Spanish perception of CSR from 2004to 2008. This is framed in a wider revision of the factors determining this perception: mass media, companies, civil society organisations, and governmental offices.The paper analyses the triple role of society (public opinion, consumers and citizens) and concludes by offering an insight into its potential development in the next two years.
Keywords: corporate social responsibility (CSR); responsible consumption; fair trade.